Human Breast Cancer Tumor Models: Molecular Imaging of Drug Susceptibility and Dosing during HER2/neu-targeted Therapy(1) - Gee, Michael S. (Radiological Society of North America, Inc., 2008)
PURPOSE: To use near-infrared (NIR) optical imaging to assess the therapeutic susceptibility and drug dosing of orthotopic human breast cancers implanted in mice treated with molecularly targeted therapy. MATERIALS AND METHODS: This study was approved by the institutional animal care and use committee. Imaging probes were synthesized by conjugating the human epidermal growth factor receptor type 2 (HER2)-specific antibody trastuzumab with fluorescent dyes. In vitro probe binding was assessed with flow cytometry. HER2-normal and HER2-overexpressing human breast cancer cells were orthotopically implanted in nude mice. Intravital laser scanning fluorescence microscopy was used to evaluate the in vivo association of the probe with the tumor cells. Mice bearing 3–5-mm-diameter tumors were intravenously injected with 0.4 nmol of HER2 probe before or after treatment. A total of 123 mice were used for all in vivo tumor growth and imaging experiments. Tumor fluorescence intensity was assessed, and standard fluorescence values were determined. Statistical significance was determined by performing standard analysis of variance across the imaging cohorts. RESULTS: HER2 probe enabled differentiation between HER2-normal and HER2-overexpressing human breast cancer cells in vitro and in vivo, with binding levels correlating with tumor trastuzumab susceptibility. Serial imaging before and during trastuzumab therapy revealed a significant reduction (P < .05) in probe binding with treatment and thus provided early evidence of successful HER2 inhibition days before the overall reduction in tumor growth was apparent. CONCLUSION: NIR imaging with HER2-specific imaging probes enables evaluation of the therapeutic susceptibility of human mammary tumors and of drug dosing during HER2-targeted therapy with trastuzumab. This approach, combined with tomographic imaging techniques, has potential in the clinical setting for determining patient eligibility for and adequate drug dosing in molecularly targeted cancer therapies. © RSNA, 2008